EFFECT OF COLCHICINE ON HUMORAL IMMUNITY AND IMMUNE ORGANS IN MICE - S. Khurram; A.Javeed1; M.Ashraf; J.Nazir; A.Ghafoor; G. Mustafa (Journal of Animal and Plant Sciences, 2017)
This study was planned to investigate effect of colchicine on humoral immune responses and immune organs in mice. Humoral immune responses were evaluated by performing haemagglutination assay, mice lethality test and Jerne hemolytic plaque formation. Colchicine treated groups were administered 40µg/kg, 80µg/kg and 160µg/kg.Data obtained was analyzed by ANOVA. There was significant(P <0.0001)reduction in HA titer of colchicine treatedgroups. With the increasing dose, there was reduction in the HA titer. Colchicine enhanced the mortality after administration of bovine Pasteurellamultocidaculture. In addition, there was significant (P<0.0001) reduction in body weight and spleen weight difference of mice in colchicine treated groups. There were no histopathological changes observed in spleen and thymus at 40µg/kg and 80µg/kg doses of colchicine. At 160µg/kg dose, increase in thickness of trabecular was seen due to edema in the spleen. This study has shown that humoral immunity is suppressed by the administration of colchicine.
Keywords: Colchicine; Humoral immunity; Immune organs